PENGARUH GROWTH SALES, PROFITABILITAS, OPERATING LEVERAGE, DAN TAX RATE TERHADAP KEBIJAKAN HUTANG - Geovana, Rosella Selvilita; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Debt policy is the policy of funding decision in which the management of the company gains the funding to finance the operational activities. The funding decision is meant to measure to what extent the company use its debt. This research is meant to test the influence of growth sales, profitability, operating leverage, and tax rate to the debt policy.The result of the research shows that the research regression models do not have any multicolinearity, heteroscedasticity, , and autocorrelation syndrome and the data has been normally distributed. The result of multiple linear regression analysis shows that growth sales has positive influence to the debt policy; profitability has negative influence to the debt policy; operating leverage has positive influence to the debt policy, and tax rate does not have any influence to the debt policy.Keywords:Growth Sales, Profitability, Operating Leverage, Tax Rate, and Debt Policy